The whispers of war - Kelly, Julia, 1986- (Gallery Books, 2020)
"The start of World War II looms over three friends who struggle to remain loyal as one of them is threatened with internment by the British government, from the author of the "sweeping, stirring" (Kristin Harmel, internationally bestselling author of The Room on Rue Amélie) The Light Over London"--